Requirement of the integrin beta 3 subunit for carcinoma cell spreading or migration on vitronectin and fibrinogen (The Rockefeller University Press, 1992)
FG human pancreatic carcinoma cells use integrin alpha v beta 5 as their primary vitronectin receptor since they fail to express integrin alpha v beta 3. These cells are unable to form focal contacts, spread, or migrate on vitronectin but readily do so on collagen in a beta 1 integrin-dependent manner. Transfection of FG cells with a cDNA encoding the integrin beta 3 subunit results in the surface expression of a functional integrin alpha v beta 3 heterodimer providing these cells with novel adhesive and biological properties. Specifically, FG cells expressing beta 3 acquire the capacity to attach and spread on vitronectin as well as fibrinogen with beta 3 localization to focal contacts. Moreover, these cells gain the capacity to migrate through a porous membrane in response to either vitronectin or fibrinogen. These results demonstrate that the beta 3 and beta 5 integrin subunits when associated with alpha v, promote distinct cellular responses to a vitronectin extracellular environment.